Effects of malleable kinetochore morphology on measurements of intrakinetochore tension. Issue 7 (8th July 2020) - Renda, Fioranna; Magidson, Valentin; Tikhonenko, Irina; Fisher, Rebecca; Miles, Christopher; Mogilner, Alex; Khodjakov, Alexey
Abstract : Abstract : The distance between fluorescent spots formed by various kinetochore proteins (delta) is commonly interpreted as a manifestation of intrakinetochore tension (IKT) caused by microtubule-mediated forces. However, large-scale changes of the kinetochore architecture (such as its shape or dimensions) may also contribute to the value of delta. To assess contributions of these non-elastic changes, we compare behaviour of delta values in human kinetochores with small yet mechanically malleable kinetochores against compound kinetochores in Indian muntjac (IM) cells whose architecture remains constant. Due to the micrometre-scale length of kinetochore plates in IM, their shape and orientation are discernible in conventional light microscopy, which enables precise measurements of IKT independent of contributions from changes in overall architecture of the organelle. We find that delta in IM kinetochores remains relatively constant when microtubule-mediated forces are suppressed by Taxol, but it prominently decreases upon detachment of microtubules. By contrast, large decreases of delta observed in Taxol-treated human cells coincide with prominent changes in length and curvature of the kinetochore plate. These observations, supported by computational modelling, suggest that at least 50% of the decrease in delta in human cells reflects malleable reorganization of kinetochore architecture rather than elastic recoil due to IKT.